Kedudukan Akta Notaris dalam Proses Legalitas Koperasi Simpan Pinjam - Giani Prani Putri Prasasti; Feira Wafi Sakina; Gani Munggaran; Elisatris Gultom (Pusat Riset dan Inovasi Nasional, 2025)
Cooperatives are business entities that carry out their activities by collecting and distributing funds. The legal basis for Cooperatives is regulated in the Constitutional Court Decision No. 28/PUU-IX/2013 concerning the cancellation of the entire Law No. 17 of 2012 concerning Cooperatives, then there was a shift in the regulations of the Law on Cooperatives, which temporarily returned its legal basis to Law Number 25 of 1992 concerning Cooperatives until the issuance of a new Law on Cooperatives. The method used in this study is descriptive analytical with a normative legal research approach method and a qualitative legal analysis method. This study is expected to provide an understanding of the role and responsibilities of Notaries related to the Deed of Establishment of Savings and Loan Cooperatives and the legal consequences for the establishment of Cooperatives that are not accompanied by a Notarial Deed. The role and responsibilities of Notaries related to the Deed of Establishment of Savings and Loan Cooperatives are to make authentic deeds that function as valid evidence of the implementation of a legal act related to the establishment, changes to the articles of association, and other deeds related to cooperative activities. The legal consequences for the establishment of a cooperative that is not accompanied by a notarial deed are contained in the Constitutional Court Decision Number 28/PUU-XI/2013 which reads as follows: Notaries are no longer permitted to prepare cooperative deed of establishment based on the procedures and methods regulated in Law Number 17 of 2012 concerning Cooperatives